Diversity and association of psychrophilic bacteria in Antarctic sea ice. - Bowman, J P (1997)
The bacterial populations associated with sea ice sampled from Antarctic coastal areas were investigated by use of a phenotypic approach and a phylogenetic approach based on genes encoding 16S rRNA (16S rDNA). The diversity of bacteria associated with sea ice was also compared with the bacterial diversity of seawater underlying sea ice. Psychrophilic (optimal growth temperature, < or = 15 degrees C; no growth occurring at 20 degrees C) bacterial diversity was found to be significantly enriched in sea ice samples possessing platelet and bottom ice diatom assemblages, with 2 to 9 distinct (average, 5.6 +/- 1.8) psychrophilic taxa isolated per sample. Substantially fewer psychrophilic isolates were recovered from ice cores with a low or negligible population of ice diatoms or from under-ice seawater samples (less than one distinct taxon isolated per sample). In addition, psychrophilic taxa that were isolated from under-ice seawater samples were in general phylogenetically distinct from psychrophilic taxa isolated from sea ice cores. The taxonomic distributions of psychrotrophic bacterial isolates (optimal growth temperature, > 20 degrees C; growth can occur at approximately 4 degrees C) isolated from sea ice cores and under-ice seawater were quite similar. Overall, bacterial isolates from Antarctic sea ice were found to belong to four phylogenetic groups, the alpha and gamma subdivisions of the Proteobacteria, the gram-positive branch, and the Flexibacter-Bacteroides-Cytophaga phylum. Most of the sea ice strains examined appeared to be novel taxa based on phylogenetic comparisons, with 45% of the strains being psychrophilic. 16S rDNA sequence analysis revealed that psychrophilic strains belonged to the genera Colwellia, Shewanella, Marinobacter, Planococcus, and novel phylogenetic lineages adjacent to Colwellia and Alteromonas and within the Flexibacter-Bacteroides-Cytophaga phylum. Psychrotrophic strains were found to be members of the genera Pseudoalteromonas, Psychrobacter, Halomonas, Pseudomonas, Hyphomonas, Sphingomonas, Arthrobacter, Planococcus, and Halobacillus. From this survey, it is proposed that ice diatom assemblages provide niches conducive to the proliferation of a diverse array of psychrophilic bacterial species.